2012
DOI: 10.1093/gerona/glr235
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Resveratrol in Older Adults With Impaired Glucose Tolerance

Abstract: At doses between 1 and 2 g/day, resveratrol improves insulin sensitivity and postmeal plasma glucose in subjects with IGT. These preliminary findings support the conduct of larger studies to further investigate the effects of resveratrol on metabolism and vascular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
225
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(237 citation statements)
references
References 34 publications
9
225
3
Order By: Relevance
“…Although these trials have used different subject groups (e.g., type 2 diabetics or older adults with glucose intolerance) and different resveratrol doses, they have indicated that resveratrol may improve insulin sensitivity. [16][17][18] Moreover, other studies have shown that resveratrol can treat organic injuries to tissues including the retina and liver by resisting oxidative stress. 19,20 To investigate the effects of resveratrol in diabetes-induced ED, we used a model of STZ-induced diabetes in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although these trials have used different subject groups (e.g., type 2 diabetics or older adults with glucose intolerance) and different resveratrol doses, they have indicated that resveratrol may improve insulin sensitivity. [16][17][18] Moreover, other studies have shown that resveratrol can treat organic injuries to tissues including the retina and liver by resisting oxidative stress. 19,20 To investigate the effects of resveratrol in diabetes-induced ED, we used a model of STZ-induced diabetes in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our moderators were unable to describe the origin of this heterogeneity, perhaps because minor experimental factors may make animals more or less sensitive to resveratrol depending on their condition. Resveratrol has shown some indication of positive effects on insulin and metabolic function in humans [17,18]. However, at a time when human trials testing for health benefits from resveratrol are in their early days, we believe it is inappropriate for resveratrol to be marketed as a lifeextending health supplement when our analysis of the current knowledge provides such varied results.…”
Section: Discussionmentioning
confidence: 99%
“…Ten patients, aged 60-80 with impaired glucose tolerance, were treated with resveratrol for 4 wk. Fasting glucose was unchanged, but postprandial glucose levels were lowered without an increase in insulin production, indicating improved insulin sensitivity [59]. Notably, the doses in the Sirtris trials (2.5-5 g/day) were in the range where gastrointestinal side effects have been reported [30], and the doses in the Crandall trial (1-2 g/day) were very close, meaning that a thorough evaluation of both the efficacy and the side effects is needed to determine the potential of resveratrol as an anti-diabetic in humans.…”
Section: Obesity and Diabetesmentioning
confidence: 96%
“…In early 2008, Sirtris Pharmaceuticals announced that their proprietary formulation of resveratrol, SRT501, had improved glucose tolerance in type II diabetics in a Phase 1b clinical trial, in the absence of serious adverse events [58]. In mid-2010, Crandall et al presented preliminary findings supporting an insulinsensitizing effect of resveratrol in humans [59]. Ten patients, aged 60-80 with impaired glucose tolerance, were treated with resveratrol for 4 wk.…”
Section: Obesity and Diabetesmentioning
confidence: 99%